What Can Be Learned from Growth Mindset Controversies? - Yeager, David S. (Am Psychol, 2020)
The growth mindset is the belief that intellectual ability can be developed. This article seeks to answer recent questions about growth mindset, such as: Does a growth mindset predict student outcomes? Do growth mindset interventions work, and work reliably? Are the effect sizes meaningful enough to merit attention? And can teachers successfully instill a growth mindset in students? After exploring the important lessons learned from these questions, the article concludes that large-scale studies, including pre-registered replications and studies conducted by third parties (such as international governmental agencies), justify confidence in growth mindset research. Mindset effects, however, are meaningfully heterogeneous across individuals and contexts. The article describes three recent advances that have helped the field to learn from this heterogeneity: standardized measures and interventions, studies designed specifically to identify where growth mindset interventions do not work (and why), and a conceptual framework for anticipating and interpreting moderation effects. The next generation of mindset research can build on these advances, for example, to begin to understand and perhaps change classroom contexts in ways that can make interventions more effective. Throughout, the authors reflect on lessons that can enrich meta-scientific perspectives on replication and generalization.